Novel approach in synthesizing graphene oxide grafted polyethylene glycol via Steglich Esterification - Ismail, Mohamad Wafiuddin; Danial, Wan Hazman; Isa, Ahmad Fida'iy (Springer Nature, 2023)
Due to its unique properties, graphene and its derivatives have been actively explored for various biological applications. However, Graphene Oxide (GO) clinical translation has been difficult due to non-specific protein adsorption and poor stability. One way to address this issue is by functionalizing GO with a biocompatible polymer, poly(ethylene glycol), PEG. Despite earlier research, the goal of this study was to establish a new method for functionalizing GO with PEG using the Steglich esterification reaction. In the esterification reaction, the carboxylate end group of PEG underwent coupling reaction with the hydroxyl group of the GO sheet to produce desired ester linkage. The fourier transform infrared spectra showed the presence of C–H stretch and C–O stretch of the PEG backbone at 2927 cm−1 and 1144 cm−1, respectively, confirmed the coupling reaction of GO-g-PEG. In the nuclear magnetic resonance analysis, a multiplet methylene peak of PEG was observed at 2.45 ppm; this peak was shifted up field to a lower ppm due to the presence of a diamagnetic ring of GO. Due to the strong intermolecular interactions between GO and PEG, thermogravimetric analysis of GO-g-PEG reveals improved thermal stability. SEM analysis shows the surface morphology of the PEG embedded on the GO indicating successful interaction via covalent bond formation between GO and the PEG. Based on the manifested result, our proposed methodology successfully showed that the PEG had attached to the hydroxyl group of GO sheets.